Salmonella enterica persister cells exhibit distinct susceptibility profiles following exposure to human serum and macrophages - Rodrigo Lira Rodrigues; Júlia Abreu da Rosa; Douglas Diefenbach da Cunha; Thaís Lima Nunes; Pedro Maria Abreu Ferreira; Bruno Kendi Makiyama; Florencia María Barbé-Tuana; Sílvia Dias de Oliveira; Carlos Alexandre Sanchez Ferreira (PLoS ONE, 2026)
Salmonella enterica , particularly non-typhoidal serovars (NTS), is a leading cause of foodborne illness, with invasive infections posing high mortality risks in developing countries. Fluoroquinolones and third-generation cephalosporins, such as ceftazidime (CAZ), are used to treat severe infections, yet they are facing concerning rates of antimicrobial resistance. Furthermore, recalcitrant and/or persistent infections are often linked to persister cells, a phenotype that enables cells to survive in the presence of high concentrations of antibiotics. Although persisters are associated with chronic infections, their interactions with the human immune system, particularly serum resistance and opsonophagocytosis, are not well understood. Here, three NTS isolates from the food protein chain (S45, S48, and 4SA(2)) were used. Persister cells were selected by exposure to CAZ concentration 100 times higher than the minimum inhibitory concentration and then assessed for serum resistance, opsonophagocytosis, and intracellular survival in primary human macrophages. The isolates exhibited heterogeneous persister fractions (1.06%–39.55% survival after 72h of CAZ exposure). Persisters exhibited equal or greater serum resistance than regular cells. Isolate 4SA(2) proliferated in 100% human serum, with persister-derived cells showing higher growth rates. Following opsonization, serum-resistant persisters of all isolates were phagocytosed at significantly higher rates than serum-resistant regular cells. Intracellular survival varied: S45 persisters proliferated post-internalization; S48 persisters and regulars were eradicated; 4SA(2) showed no phenotype difference. Complement enhanced the intracellular survival of S45 but not S48 or 4SA(2). Despite having different intracellular outcomes, Salmonella persisters showed higher levels of opsonophagocytosis and serum resistance. These findings suggest that cell surface modifications may facilitate host cell uptake and contribute to antimicrobial treatment failure and long-term infection. The phenotypic diversity among isolates underscores the importance of considering persister heterogeneity and host-pathogen immune interactions in order to understand recalcitrant infection dynamics and design more effective therapeutic strategies.